Suspected intracranial hypertension in COVID-19 patients with severe respiratory failure. - Marco Carbonara; Erica Ferrari; Tatiana Birg; Veronica Punzi; Francesca Bichi; Beatrice Lazzari; Valentina Palmaverdi; Nicola Bottino; Fabrizio Ortolano; Tommaso Zoerle; Giorgio Conte; Nino Stocchetti; et al. (PLoS ONE)
Background COVID-19 patients may exhibit neurological symptoms due to direct viral damage, systemic inflammatory syndrome, or treatment side effects. Mechanical ventilation in patients with severe respiratory failure often requires sedation and neuromuscular blockade, hindering thorough clinical examinations. This study aimed to investigate neurological involvement through clinical and noninvasive techniques and to detect signs of intracranial hypertension in these patients. Method We conducted a prospective observational study on mechanically ventilated COVID-19 adult patients admitted to our ICU, following standard of care protocols for ventilation and permissive hypercapnia. Data were collected at three time points: admission day (T1), day seven (T7), and day fourteen (T14). At each time point, patients underwent multimodal noninvasive neurological monitoring, including clinical examination, pupillary reactivity, transcranial color doppler of the middle cerebral artery (MCA), and optic nerve sheath diameter (ONSD) assessed via ultrasound (US). Head computer tomography (CT) was performed at T1 and T14. A limited subset of patients had a follow-up examination six months after ICU discharge. Results Seventy-nine patients were recruited; most were under deep sedation and neuromuscular blockade at T1. Pupillary size, symmetry, and reactivity were normal, as was the MCA mean velocity. However, ONSD, assessed by both US and CT, appeared enlarged, suggesting raised intracranial pressure (ICP). In a subgroup of 12 patients, increased minute ventilation was associated with a significant decrease in US-ONSD, corresponding to a drop in paCO2. At follow-up, twelve patients showed no long-term neurological sequelae, and US-ONSD was decreased in all of them. Discussion and conclusions In this cohort, enlarged ONSD was detected during non-invasive neurological monitoring, suggesting a raised ICP, with hypercapnia playing a prominent role. Further studies are needed to explore ONSD behavior in other samples of mechanically ventilated, hypercapnic patients.